Species Variability as a Determinant of Root Knot Nematode, Meloidogyne incognita Race 1, Resistance on Crotalaria spp. - Cheruiyot , H. K.; Omami , E.N.; Ochuodho , J. O. (African Journal of Education,Science and Technology (AJEST), 2013)
Abdul Karim, S., Yuen, P. M., & Norlia, Y. (2002). Challenges in the integrated management of the root-knot nematode on guava. Prosiding Mesyuarat Teknikal Pusat HR. Port Dickson, m.s 27. Serdang: MARDI. Agrios, G. N. (2005). Plant Pathology (5th ed.). Academic Press. USA. pp. 635. Ameer-Zareen, Zaki, J.M. & Javed, N. (2003). Nematicidal activity of ginger and its effect on the efficacy Pasteuria penetrans for the control of root knot nematodes. Asian Journal of Plant Sciences, 2(11), 858-860. Anwar, S. A., McKenry, M. V., & Legari, A.U. (2009a). Host suitability of sixteen vegetable crop genotypes for Meloidogyne incognita. Journal of Nematology, 41, 64-65. Cayuela, M. L., Millner, P. D., Meyer, S. L. F., & Roig, A. (2008). Potential of olive mill waste and compost as biobased pesticides against weeds, fungi, and nematodes. Science of the Total Environment, 399, 11-18. Cervantes-Flores, J. C., Yencho, G. C., Pecota, K. V., Sosinski, B., & Mwanga, R. O. M. (2008). Detection of quantitative trait loci and inheritance of root-knot nematode resistance in sweetpotato. Journal of American Society of Horticultural Sciences, 133, 844-851. Cetintas, R., & Yarba, M. M. (2010). Nematicidal Effects of Five Essential Plant Oils on the Southern Root-Knot Nematode, Meloidogyne incognita Race 2. Journal of Animal Veterinary Advances, 9, 222-225. Chitwood, D. J. (2002). Phytochemical based strategies for nematode control. Annual Review of Phytopathology, 40, 221-249. Cook, R., & Evans, K. (1987). Resistance and tolerance. In R. H. Brown, & B. R. Kerry, (Eds.), Principles and practice of nematode control in crops (pp. 179-231). London: Academic Press. Eisenback, J. D., Hirschmann, H. J. N., Sasser, J. N., & Triantaphyllou, A. C. (1981). A guide to the most common species of root knot nematode (Meloidogyne spp.), with a pictorial key. North Carolina State University/USAID, Raleigh, NC. Fassuliotis, G. (1969). Plant breeding for root-knot nematode resistance. In F. Lamberti, & C. E. Taylor (Eds.), Root-knot nematodes (Meloidogyne species) Effects on nutrient cycling and plant growth (pp. 425-453). Ecological Monographs. Hartman, K. M., & Sasser, J. N. (1985). Identification of Meloidogyne species on the basis of incognita and M. javanica. Annuals of Tropical Resources Philippines, 8(4), 176-188. Inomoto, M. M. (1994). Host reaction of some plant species to the burrowing nematode. Nematologia Brasileira, 18, 21-27. Jepson, S. B. (1987). Identification of root –knot nematodes. CAB international, Wallingford. Karssen, G. (2002). The plant-parasitic nematode genus Meloidogyne Göldi (Tylenchida) in Europe. Koninklijke Brill NV, Leiden, The Netherlands. p. 157. Khan, A., Shaukat, S. S., & Siddiqui, I. A. (2005). A survey of nematodes of pomegranate orchards in Balochistan province. Pakistan. Nematologia Mediterrannean, 33, 25-28. Lazzeri L., Curto, G., Leoni, O., & Dallavalle, E. (2004). Effects of glucosinolates and their enzymatic hydrolysis products via differential host test and perinneal-pattern morphology, p. 69-77. Le Roux, M. M.,Van Wyk, B.E., Moteetee, A.N. & Tilney, P.M. (2009). An evaluation ofmolecular and anatomical characters in the genus Crotalaria. South African Journal of Botany, 75, 410. McKenry, M. V., & Anwar, S. A. (2006). Nematode and grape rootstock interactions including an improved understanding of tolerance. Journal of Nematology, 38, 312-318. McSorley, R. (1999). Host suitability of potential cover crops for root-knot nematodes. Journal of Nematology, 31, 619-623. Nogueira M. A., de Oliveira, J. S., Ferraz, S., & Dos Santos, M. A. (1996). Nematicidal constituents in Mucuna aterrima and its activity on Meloidogyne incognita race 3. Nematologia Meditterenean, 24, 249-252. Oostenbrink, M. (1966). Major characteristics of the relation between nematodes and plants. Mededelingen voor Landbouwhogeschool Wageningen, 66, 3-46. Quesenberry, K. H., Baltensperger, D. D., Dunn, R.A., Wilcox, C. J., & Hardy, S. R. (1989). Selection for root-knot nematodes in red clover. Crop Sciences, 29, 62-66. Santos, M. A., & Ruano, O. (1987). Reac¸a˜o de plantas usadas como adubos verdes a Meloidogyne incognita race 3 M. javanica. Nematologia Brasileira, 11, 184-197. Scurrah, M. L., Niere, B., & Bridge, J. (2005). Nematode parasites of solanum and sweet potatoes. In M. Luc, R. A. Sikora, & J. Bridge, (Eds.), Plant Parasitic Nematodes in Subtropical and Tropical Agriculture (pp. 193-219). CABI Publishing, Wallingford, UK. Taylor, A. L., Sasser, J. N., & Nelson, L. A. (1982). Relationship of climate and soil characteristics to geographical distribution of Meloidogyne species in agricultural soils. International. Meloidogyne Project. Raleigh, N.C. Wang, K. H., Sipes B. S. & Schmitt D. P. (2001). Suppression of Rotylenchulus reniformis by Crotalaria juncea, Brassica napus, and Tagetes erecta. Nematropica, 31, 237-251. Wang, K. H., McSorley, R., Marshall, A. J., & Gallaher, R. N. (2002b). Nematode community changes associated with decomposition of Crotalaria juncea amendment in litterbags. Applied Soil Ecology, 27, 31-45. Wuyts, N., Swennen, R., & De Waele, D. (2006). Effects of phenylpropanoid pathway products and selected terpenoids and alkaloids on the behaviour of plant parasitic nematodes Radopholus similis, Pratylenchus penetrans and Meloidogyne incognita. Nematology, 8, 89-101. Zhang, F., & Schmitt, D. P. (1994). Host Status of 32 plant species to Meloidogyne konaensis. Journal Nematology, 26, 744-748. Taylor, A. L. & Sasser, J. N. (1978). Biology, identification and control of root not nematodes (Meloidogyne spp). Coop. publication. Department of Plant Pathology, North Carolina State University and U.S. Agency International Development. Raleigh, North Carolina. p. 111.